The role of agile values in enhancing good governance in public administration during the COVID-19 crisis: An international survey - Nina Tomaževič; Polonca Kovač; Dejan Ravšelj; Lan Umek; Cenay Babaoğlu; Marie Bohatá; Bernhard Hirsch; Onur Kulaç; Guliya K. Nurlybaeva; Fabienne-Sophie Schäfer; Aleksander Aristovnik (Administrative Sciences, 2023)
This study aimed to analyse the impact of digitalisation on good governance with respect to selected local public administrations during the COVID-19 lockdown in the spring of 2020. The overriding assumption made is that agile values mediate the relationship between digitalisation and good governance on this level of public administration. Data were obtained through a web-based survey conducted between June and August 2020. The empirical analysis was facilitated by applying partial least squares structural equation modelling (PLS-SEM) on a sample of 761 public managers from five Central European countries (Czech Republic, Germany, Poland, Romania, Slovenia). The results show that digitalisation acted as an essential driver of good governance during the COVID-19 pandemic. Three out of four agile values-"employees and internal relationships", "working public services", and "change management"-were also shown to help make digitalisation more effective and thereby facilitate good governance. Despite some limitations (e.g., respondents' subjective evaluations, the study only being performed during the first wave of the COVID-19 pandemic in the observed countries with different situations and consequent measures in response, and differences in the broader environment and local administration systems in the studied countries), the findings of the study are important given the lack of similar empirical studies. Public administrations should be digitalised and reformed in a way that ensures that they effectively and efficiently design, implement, measure, and continuously improve their strategies, tactics, and services, which can all be accomplished by being agile. The paper offers insights into: (1) the lessons learnt about the nature of digitalised public services/processes and agile management approaches in response to the COVID-19 pandemic and their impact on good governance; and (2) proposals for policymakers and managers in public administrations with regard to operating in extreme VUCA circumstances in any next wave of COVID-19 pandemic or in a new pandemic/public health disaster.
Keywords: 350; agile; agile values; COVID-19 pandemic; digitalisation; good governance; local public administration; PLS-SEM; public managers